A new fault-tolerant architecture based on DASH for adaptive streaming video. (2017) - Harrouch, Haifa; Kaddes, Mourad; Abdouli, Majed; Duvallet, Claude; Bouaziz, Rafik
The standard dynamic adaptive streaming over HTTP (DASH) has been proposed to guarantee a quality of video under varying bandwidth. DASH enables adaptation of the media bit-rate to varying throughput conditions by offering multiple representations of the same content. However, the Moving Picture Experts Group (MPEG) DASH specification only defines the media presentation description (MPD) and the segment formats. In order to take advantages of DASH, we propose a fairness architecture, called dynamic adaptive streaming over HTTP distributed multimedia systems (DASH-DMS). DASH-DMS combines both 2-tiers and 3-tiers architectures in order to guarantee a quality of service (QoS) under changing conditions. Moreover, we propose replication algorithms to enable load balancing video servers and improve the global QoS. Furthermore, in order to improve the availability of our system, we use a fault tolerance policy. To this purpose, we have conduct simulations throughout the paper using the simulator developed by our team.